If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65 + -2x = 16x + 19 Reorder the terms: 65 + -2x = 19 + 16x Solving 65 + -2x = 19 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 65 + -2x + -16x = 19 + 16x + -16x Combine like terms: -2x + -16x = -18x 65 + -18x = 19 + 16x + -16x Combine like terms: 16x + -16x = 0 65 + -18x = 19 + 0 65 + -18x = 19 Add '-65' to each side of the equation. 65 + -65 + -18x = 19 + -65 Combine like terms: 65 + -65 = 0 0 + -18x = 19 + -65 -18x = 19 + -65 Combine like terms: 19 + -65 = -46 -18x = -46 Divide each side by '-18'. x = 2.555555556 Simplifying x = 2.555555556
| 6-7x=16-14x | | -51-8x=7x+24 | | 5x+10=-120-8x | | 25*6= | | 10a^2=3(7a-3) | | 350=2(6w)+2w | | 82-2x=3x+7 | | 9(w^2+1)=9-w | | 3e(3e-1)=2 | | 10t^2-3t-1=0 | | 8x-y=22 | | 3h^2-4h+1=0 | | 5x+7=2x-2 | | 9x+5=3x+35 | | 10y^2-30y-2=0 | | 3x^2+26x+35=0 | | 4*2+3= | | 9(11+k)=3(3k-9) | | 30=2(2x+3)+2x | | 6(1+c)=c-c^2 | | 4x^3+8x^2-96x=0 | | 9x-21=3x+3 | | 6(1tc)=c-c^2 | | 102-75=31y-40y | | 3x^2+6x+3=0 | | r^2+2=11 | | b^2=12(b-3) | | -5(2p+3)-29=3(5p+2) | | 7.1=ax+b | | 2.5=3n | | y=ax+b | | 2p-12p=90 |